Some practical issues about the relationship between national science and technology program with the national strategy for science, technology and innovation development - Ha Cong Hai (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2022)
The National Science and Technology (S&T) Program has a close relationship with the National Strategy for Science, Technology and Innovation (STI) development. The National S&T Program is a part of the National Strategy for STI development, a tool of operation of the Strategy to bring the Strategy’s priority orientations into the of socio-economic reality. In the period 2011-2020 in Vietnam, National S&T Program system had 35 programs, of which nearly 40% of the programs are designed independently and not geared towards the implementation of the Strategy, remaining programs are designed directly and indirectly to implement/concretize the priority orientations of the Strategy. However, with a large number of national-level S&T programs under a constraint investment resources, the investment level for a National S&T Program is still low, and not efficient to achieve the goals of the program and the Strategy. This article focuses on clarifying the main issues and shortcomings in the relationship between the National S&T Program and the National S&T development Strategy for the period 2011-2020, thereby suggesting some solutions to strengthen the relationship between National S&T Program with the National Strategy for STI development to 2030 in Vietnam. Code: 22010701